Catalytic Synthesis of Formamides by Integrating CO2 Capture and Morpholine Formylation on Supported Iridium Catalyst. Issue 26 (3rd May 2022) - Cheng, Danyang; Wang, Meng; Tang, Lipeng; Gao, Zirui; Qin, Xuetao; Gao, Yongjun; Xiao, Dequan; Zhou, Wu; Ma, Ding
Abstract: Herein we report an efficient and recyclable catalytic system for tandem CO2 capture and N‐formylation to value‐added chemicals. CO2 is apt to be captured by morpholine solution, while a highly efficient heterogeneous catalyst, isolated iridium atoms supported over nanadiamond/graphene, is discovered to be highly reactive for the formylation of morpholine, leading to the formation of N‐formylmorpholine with excellent productivity (with a turnover number of 5 120 000 in a single batch reaction) and selectivity (>99 %). In addition, the CO2 captured by morpholine under atmospheric conditions can be converted to N‐formylmorpholine with decent conversion (51 %), which realizes the integration of CO2 capture and conversion to value‐added chemicals. Abstract : Morpholine is used as CO2 capture and formylation reagent to get value‐added N‐formylmorpholine under relatively mild reaction conditions. Morpholine can capture CO2 in air efficiently and be further hydrogenated to formamides on isolated Ir/ND@G catalysts with a TON up to 817 000.